Significantly enhanced stability and activity of a perovskite oxygen electrode for reversible protonic ceramic electrochemical cells by heterointerface engineering - Xiaoyu Zhang; Chenxiao Wang; Kui Liu; Yucun Zhou; Zuzhi Huang; Ting Chen; Guangjun Zhang; Ning Sun; Zichen Zhuang; Lang Xu; Shaorong Wang (Journal of Advanced Ceramics)
Reversible protonic ceramic electrochemical cells (R-PCECs), which are capable of efficiently converting electrical and chemical energy in mutual directions, are considered highly promising alternatives for bidirectional electrical energy generation or storage. However, the sluggish electrocatalytic activity at low temperatures and unsatisfactory operational durability of oxygen electrodes remain the primary challenges to the commercial application of R-PCECs. Here, the degradation mechanism of the BaFe0.4Co0.4Zr0.1Y0.1O3−δ (BFCZY) oxygen electrode under humid conditions is systematically investigated. This degradation can be attributed to the formation of BaCO3 caused by water-facilitated Ba segregation. The activity and stability of the BFCZY oxygen electrode are significantly improved through heterointerface engineering by infiltrating the BaCoO3 (BCO) catalyst. At 600 °C in 30 vol% H2O–air, heterointerface engineering decreases the polarization resistance of the BFCZY electrode by half (from 0.42 to 0.21 Ω·cm2) and the decay rate by more than one order of magnitude (from 0.384 to 0.026 Ω·cm2/100 h). Moreover, an R-PCEC with a BCO–BFCZY oxygen electrode exhibited high activity and stability in both fuel cell and water electrolysis modes. The substantially increased electrocatalytic activity and stability of the oxygen electrode are attributed primarily to the improved surface oxygen exchange process and inhibited Ba segregation.